Ultra low-power filter bank for hearing aid speech processor - Chong, Kwen-Siong (2013)
An ultra-low power sub-threshold Finite Impulse Response (FIR) filter bank for hearing aid applications is demonstrated in 65nm CMOS technology. The system has a 2kb Static Random Access Memory (SRAM) interface optimized for sub-threshold operation. The system operates at 0.3V sub-threshold regime and consumes 10.4 μW at 0.96MHz clock frequency which corresponds to merely 0.6nJ per FIR operation.